Description of Depression Level in Coronary Heart Disease Patients at RSPAD Gatot Soebroto in 2021 - Elly Tania; Andri Andri (Jurnal MedScientiae, 2022)
Coronary heart disease (CHD) is a chronic disease that lasts a long time and requires long-term treatment, besides those physical conditions can also have an impact on a person's psychological condition, one of which is depression. However, it is possible that depression can also cause coronary heart disease in a person. Symptoms often overlap with cardiac symptoms, such as fatigue and insomnia (difficulty sleeping) which makes it difficult to diagnose depression in coronary heart disease patients. This study aims to determine the description of depression in coronary heart disease so that it can provide benefits in the form of knowledge about depression in coronary heart disease. The results of the data analyzed found the majority of respondents 93.3% had minimal or normal depression, 2.9% had mild depression, 1.9% had moderate depression and 1.9% had severe depression. The conclusion obtained from this study is that most of the respondents experienced minimal or normal depression, there was no difference between women and men, and there was no decrease in the quality of life of the respondents, such as feeling tired easily and having trouble sleeping.